Imagined communisms: the Argentine new left and the construction of “Real socialism” in the 1960s/1970s - Lucas Duarte (RUDN Journal of World History, 2025)
This research analyzes the readings and interpretations produced by an Argentine political organization, the Partido Revolucionario de los Trabajadores - Ejército Revolucionario del Pueblo (PRT-ERP), regarding the construction of socialism in countries such as the Soviet Union, China, and various locations in Eastern Europe during the 1960s and 1970s. Our objective is to trace the impact produced by these experiences on the revolutionary horizon adopted by the party, examining how they were incorporated into its intervention platform over time. We observe how everyday life, development projects, and different political, diplomatic, and cultural initiatives led by countries associated with the “real socialism” universe were represented in the PRT-ERP’s periodicals, Estrella Roja and El Combatiente, and debated in its internal documentation. The analysis of documentary sources indicates that, despite being associated with the universe of the so-called “new lefts”, which emerged globally throughout the second half of the 20th century, the PRT-ERP was particularly interested in understanding what it called “the construction of socialism” in Eastern countries. This finding allows for a review of some definitions about the expectations that guided the actions of young people, women, and workers involved in Southern Cone (Brazil, Chile, Argentina, Paraguay, Peru and Uruguay) revolutionary organizations during the 1960s and 1970s. Far from being an exception, the PRTERP was one of the most notable expressions of the phenomenon of political radicalization that crossed the regional landscape during that period.